Invertebrate models of behavioural plasticity and human disease. (December 2018) - Holden-Dye, Lindy; Walker, Robert J.
The fundamental processes of neural communication have been largely conserved through evolution. Throughout the last century, researchers have taken advantage of this, and the experimental tractability of invertebrate animals, to advance understanding of the nervous system that translates to mammalian brain. This started with the inspired analysis of the ionic basis of neuronal excitability and neurotransmission using squid during the 1940s and 1950s and has progressed to detailed insight into the molecular architecture of the synapse facilitated by the genetic tractability of the nematode Caenorhabditis elegans and the fruit fly Drosophila melanogaster . Throughout this time, invertebrate preparations have provided a means to link neural mechanisms to behavioural plasticity and thus key insight into fundamental aspects of control systems, learning, and memory. This article captures key highlights that exemplify the historical and continuing invertebrate contribution to neuroscience.